Developing a Simplified Analytical Thermal Model of Multi-chip Power Module. (November 2016) - Bouguezzi, Sihem; Ayadi, Moez; Ghariani, Moez
Abstract: The study of the thermal behavior of power modules has become a necessity regarding the known rapid development in modern power electronics, and the prediction of temperature variation has generally been performed using transient thermal equivalent circuits. In this paper we have developed a simplified analytical thermal model of a power hybrid module. This analytical method is used to evaluate the thermal parameters of a device. The model takes into account the thermal mutual influence between the different module chips based on the analytical method. The thermal interaction between components is dependent on the boundary condition, the dissipated power value in the different components and the number of operating chips constituting the module. This effect is modelled as a source energy and a thermal resistance simply computed tanks to reasonably low measurement applied on the module. The derived thermal models offer an excellent trade-off between accuracy, efficiency and CPU-cost. Highlights: A behavioral thermal model of multi-chips power module is presented. We have presented a simplified analytical method for evaluating the transient response of the studied power module. We have developed an RC thermal model which is compatible with circuit simulators. The model takes into account the thermal mutual influence between the different module chips. Numerical simulations and experiments are performed in order to validate the proposed model.